Prognostic significance of systemic inflammatory markers in rectal cancer (Annals of Medical Research, 2021)
Aim: The neutrophil-lymphocyte ratio (NLR) and the platelet-lymphocyte ratio (PLR), which is indicators of systemic inflammatory response, have been demonstrated to be prognostic factors in many types of cancer. The aim of this study was to investigate importance of NLR and PLR in rectal cancer.Materials and Methods: The data of 114 patients who underwent curative resection after neoadjuvant chemoradiotherapy (NACRT) for rectal cancer (RC) between January 2012 to June 2017 and 113 healthy subjects were retrospectively analyzed. Blood samples obtained prior to NACRT were examined. The NLR and PLR in RC patients were compared with the results of healthy individuals.Results: The distribution of NLR and PLR results was significantly different between the RC patients and the control group (p0.001 for both). According to the ROC curve, the cut-off value for NLR was 2.70 and for PLR it was 151.18 in estimating the survival of the patients. NLR and PLR only correlated significantly with tumor wall involvement (T stage). The Kaplan-Meier method of predicting survival revealed no significant difference between groups with increased or decreased NLR and PLR in terms of overall survival (OS) and disease-free survival (DFS).Conclusion: The NLR and PLR of the study group treated with NACRT and those of the control group were significantly different. However, elevated NLR and PLR before NACRT were not found to be significant prognostic biomarkers for OS and DFS in surgically treated RC patients.
Keywords: Neutrophil-lymphocyte ratio; platelet-lymphocyte ratio; rectal cancer; systemic inflammatory indicators